Análise qualitativa de superfície do pavimento asfáltico do Campus Universitário da UFAM - Rodrigues, Felipe Lopes (Brasil, 2024)
The transportation infrastructure in Brazil has been marked by the importance and necessity of the road transport mode, with its main biases being the transportation of goods and people. That said, road logistics, as well as its physical condition, can be considered a link of great importance to society. However, this preference faces significant challenges, especially evidenced by the poor condition of roads, particularly in the Northern region of the country. The lack of effective maintenance measures exacerbates the situation, compromising the quality of services and the safety of users. The use of materials that meet regulatory standards is vital to ensure the quality of roads, with asphalt pavement, especially Asphalt Concrete, being the most widely used in Brazil. The qualitative analysis of pavement surfaces becomes an essential field of study, given the relevance of road transport in the national scenario. This research focused on the analysis of flexible pavement at the UFAM University Campus, where its operational quality directly impacts the mobility and safety of the academic community. Four sections were identified, each 10 meters in length at intervals of 100 meters, each considered critical in terms of the emergence of pathologies. The defects present on the road were examined in detail and objectively, and the normative parameters established by DNIT were verified. Thus, after the survey of pathologies and deflections, the Global Severity Index (IGG) was calculated, which classifies the operational condition of the road and can serve as a determining factor in choosing the appropriate treatment for the road. For the case study in question, sections 1 and 2 were classified as poor, and sections 3 and 4 as fair, indicating that the conditions of the analyzed sections are below the recommended standard. Finally, there was a discussion regarding the pathologies present in sections 1 and 2, considering that these sections underwent recent maintenance. Therefore, it was expected that their functional assessments would not be the most critical.